Socio-emotional competences and resilience of students from vulnerable schools and their relationship with academic performance - Suárez Cretton, Ximena (2022)
The study is situated in the sociocultural context of the vulnerability of the child population of the Araucanía region, which characterizes it as one of the poorest regions of Chile and with lower indicators of educational level. The purpose is to explore the level of development of socio-emotional skills and their relationship with academic performance. The variables to be investigated are the potential for socio-emotional adaptation and the capacity for childhood resilience, and their relationship with school performance. The sample consisted of children 718 from 5th to 8th grade of basic education of vulnerable municipal schools in the province of Malleco. The collection of information was carried out using two instruments: The School Resilience Scale (ERE) of Saavedra y Castro (2008); the Socio-Emotional Adaptation Questionnaire for Schoolchildren, validated in Chile by Mathiesen, Merino; Castro, Mora and Navarro (2011). The results obtained reveal a good level of development of the social-emotional and resilience skills in children, and a positive correlation of these with academic performance. The good level of socio-emotional variables in students connotes a protective factor of mental health, a resource to compensate for the effects of vulnerability and a potential to be used to improve academic performance. Confirm the relevance of the intervention in socio-emotional skills.